2015
DOI: 10.1007/s10549-015-3653-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of guideline-based use of uPA/PAI-1 on patient outcome in intermediate-risk early breast cancer

Abstract: The purpose of this study was to evaluate the influence of guideline-based prospective use of uPA/PAI-1 on clinical outcome in an intermediate-risk cohort of breast cancer patients. We analyzed 381 consecutive primary breast cancer patients (2003-2011) at the breast center Ostbayern meeting the following criteria: M0/N0/estrogen receptor (ER)+/G2. Clinical-pathological data, uPA/PAI-1, and follow-up data were collected. Decisions for adjuvant chemotherapy were made upon consideration of prospectively measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
4
7
0
Order By: Relevance
“…EPclin and uPA/PAI-1 have been validated for risk stratification of patients with endocrine sensitive early breast cancer and have been used already for some time in clinical routine. The risk stratification performed in the context of the present study by uPA/PAI-1 (46% low risk, 54% high risk) and EPclin (63% low risk, 37% high risk) is consistent with published data from other retrospective, monocentric surveys; recently, Kolben et al reported about 381 intermediate-risk patients, of which 45% were uPA/PAI-1 low risk and 55% were uPA/PAI-1 high risk [ 24 ]. Müller et al report a EPclin low-risk group of 48% in a cohort of 167 defined tumors in which smaller tumors (pT1a/b) were under-represented compared to the present study [ 20 ].…”
Section: Discussionsupporting
confidence: 90%
“…EPclin and uPA/PAI-1 have been validated for risk stratification of patients with endocrine sensitive early breast cancer and have been used already for some time in clinical routine. The risk stratification performed in the context of the present study by uPA/PAI-1 (46% low risk, 54% high risk) and EPclin (63% low risk, 37% high risk) is consistent with published data from other retrospective, monocentric surveys; recently, Kolben et al reported about 381 intermediate-risk patients, of which 45% were uPA/PAI-1 low risk and 55% were uPA/PAI-1 high risk [ 24 ]. Müller et al report a EPclin low-risk group of 48% in a cohort of 167 defined tumors in which smaller tumors (pT1a/b) were under-represented compared to the present study [ 20 ].…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have shown that the use of uPA/PAI-1 combined with a clinicopathological parameter, such as vascular invasion, is extremely helpful for yielding prognostic data [ 24 ]. We identified a correlation between Ki67 and uPA/PAI-1 status in grade II tumours, in agreement with Kolben et al [ 25 ], although we lack an explanation for this correlation.…”
Section: Discussionsupporting
confidence: 91%
“…This rate of indication for adjuvant chemotherapy (i.e. 6%) was similar to that in a previous report [ 27 ], but lower than the rate of 13% reported by Kolben et al [ 25 ]. However, the cut-off value for Ki67 in those studies was different from that in the current study (10–15% in Kolben et al and Vénat-Bouvet et al vs. 20% in our study).…”
Section: Discussionsupporting
confidence: 89%
“…We observed that the expression of these proteins in pre-treatment tumor biopsies could be used to identify patients with a high probability of death and to distinguish them from patients with low risk. Many studies in breast cancer patients, have establish SERPINE1 and uPA as suitable markers for therapy decision-making in patients with early lymph-node negative breast cancer [ 143 - 146 ]. We expect that these markers will be increasingly studied in the near future to establish if they could also be used in HNSCC patients for helping treatment decision making, especially to identify those patients with a high risk of metastasis who could be treated with adjuvant chemotherapy or chemo-radiation.…”
Section: Serpine1 Upa and Upar Expression As Prognostic Markers In Hmentioning
confidence: 99%